Deep Learning with TensorFlow 2 and Keras : Regression, ConvNets, GANs, RNNs, NLP, and more with TensorFlow 2 and the Keras API. /: Regression, ConvNets, GANs, RNNs, NLP, and more with TensorFlow 2 and the Keras API. (2019) - Gulli, Antonio
No abstract available